2022
DOI: 10.1302/2633-1462.32.bjo-2021-0160.r1
|View full text |Cite
|
Sign up to set email alerts
|

A Preoperative Spinal Education intervention for spinal fusion surgery designed using the Rehabilitation Treatment Specification System is safe and could reduce hospital length of stay, normalize expectations, and reduce anxiety

Abstract: Aims Psychoeducative prehabilitation to optimize surgical outcomes is relatively novel in spinal fusion surgery and, like most rehabilitation treatments, they are rarely well specified. Spinal fusion patients experience anxieties perioperatively about pain and immobility, which might prolong hospital length of stay (LOS). The aim of this prospective cohort study was to determine if a Preoperative Spinal Education (POSE) programme, specified using the Rehabilitation Treatment Specification System (RTSS) and des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…24 A recent prospective study conducted by Edwards et al found that a preoperative spinal education (POSE) program was associated with a significant reduction in the length of hospital stay post lumbar fusion surgery, thereby supporting the use of preoperative programs. 22 Overall, these study results strengthen the case for incorporating prehabilitation education programs in spine surgery.…”
Section: General Education-based Prehabilitation (N = 6)supporting
confidence: 58%
See 1 more Smart Citation
“…24 A recent prospective study conducted by Edwards et al found that a preoperative spinal education (POSE) program was associated with a significant reduction in the length of hospital stay post lumbar fusion surgery, thereby supporting the use of preoperative programs. 22 Overall, these study results strengthen the case for incorporating prehabilitation education programs in spine surgery.…”
Section: General Education-based Prehabilitation (N = 6)supporting
confidence: 58%
“…General education-based prehabilitation made up 26% of the 23 eligible studies. These studies consisted of randomized clinical trials (n = 2, 8.6%), 20,21 prospective cohort studies (n = 2, 8.6%), 22,23 and retrospective cohort studies (n = 2, 8.6%). 24,25 These studies used different prehabilitation education strategies including in-depth information about the surgical procedure, reasons for having the surgery, expectations, risks, limitations, recovery process, and pain experience.…”
Section: General Education-based Prehabilitation (N = 6)mentioning
confidence: 99%
“…37 Given the importance of adherence to postoperative instructions and physiotherapy, preoperative intervention to lessen the psychological burden and properly define the patient’s expectations from surgery may be vital in improving both the patient-reported and structural outcomes of ASD surgery. 38,39…”
Section: Discussionmentioning
confidence: 99%
“…37 Given the importance of adherence to postoperative instructions and physiotherapy, preoperative intervention to lessen the psychological burden and properly define the patient's expectations from surgery may be vital in improving both the patientreported and structural outcomes of ASD surgery. 38,39 Osteoporosis and obesity were more problematic conditions in younger patients, and their impact was modulated by the severity of baseline deformity. The adverse impact of obesity and osteoporosis has also been highlighted in several areas of spine surgery, including deformity correction.…”
Section: Discussionmentioning
confidence: 99%
“…how the ingredients affect the target) (8). To date, published application of the RTSS have demonstrated the ability of the RTSS to map targets and ingredients to a patient population or therapy discipline using previous research (9)(10)(11)(12)(13)(14). Yet understanding clinicians' experiences utilizing the RTSS and any effects it has on clinical rehabilitation practice remains to be understood.…”
Section: Introductionmentioning
confidence: 99%